PERENCANAAN MANAJEMEN MUTU LAYANAN PERPUSTAKAAN DI SMP NEGERI 1 BABAKANCIKAO PURWAKARTA - Hamilah; Muhamad Taufik BK; Muchdjabir Wahid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The school library plays an important role in supporting the learning process and improving students’ reading interest. However, the success of library services is highly influenced by effective planning in quality management. This study aims to examine the planning (Plan) stage of library service quality management at SMP Negeri 1 Babakancikao Purwakarta in an effort to enhance students’ reading interest. This research employed a descriptive qualitative approach involving the principal, librarian, and students as research subjects. Data were collected through interviews, observations, and documentation, and then analyzed descriptively to obtain an in-depth understanding of library service planning. The results revealed that library service planning had been carried out systematically through the development of long-term, medium-term, annual, and library service programs adjusted to students’ needs and school conditions. The planning was implemented through literacy activities, reading corners, digital library services, book procurement funded by the School Operational Assistance (BOS) program, and collaboration with the regional library. In addition, the school sought to identify students’ needs and reading interests by providing various types of attractive reading materials. Nevertheless, several obstacles were found, including limited facilities, insufficient diversity of reading collections, and the absence of regular reading habits among students. It can be concluded that the planning of library service quality management has been implemented well; however, improvements in facilities, expansion of reading collections, and strengthening of literacy programs are still needed to optimize students’ reading interest.